Manajemen Nyeri Post Operasi Menggunakan Metode Benson di RSI Banjarnegara - Ramdani, Egi Hilmi; Suryani, Roro Lintang; Burhan, Asmat (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Background: Postoperative pain is caused by wound stimulation that triggers the body to produce chemical mediators that cause pain. Nurses can detect it through patient complaints and physiological responses. Approximately 50% of elective postoperative patients experience pain, which is at risk of increasing chronic pain and reducing satisfaction with health services. One non-pharmacological approach to dealing with this pain is the Benson relaxation technique, which is a development of deep breathing and involves patient beliefs, helping to reduce pain by creating a calm environment and a relaxed body. Objective: The program for implementing postoperative pain management using the Benson relaxation method at RSI Banjarnegara aims to provide a demonstration to postoperative patients with 30 respondents to use the Benson relaxation method to reduce postoperative pain. In addition, this activity aims to increase the knowledge of postoperative patients if pain occurs, patients can overcome it with non-pharmacological therapy independently. Method: This PKM method applies the Benson relaxation technique as an approach to nursing care for postoperative patients who experience pain. Community service activities are carried out by implementing directly by applying the Benson Relaxation technique. The target of this PKM is patients who have undergone surgery at RSI Banjarnegara. Results: The results obtained from the community service at RSI Banjarnegara from 30 respondents who participated in this activity showed the level of pain before being given Benson relaxation therapy: mild pain (40%), moderate pain (50%), and severe pain (10%), with the majority in the moderate pain category (50%). Then after Benson relaxation therapy was given, mild pain increased to 80%, moderate pain decreased to 20%, and severe pain became 0%. Benson therapy significantly reduced the level of pain, from an average of moderate pain (50%) to mild pain (80%). And for the participants of this PKM activity, they also gained knowledge about how to reduce pain with non-pharmacological therapy, namely the Benson relaxation technique. Output: The output of this PKM activity is in the form of leaflets and publication articles that can be used to increase insight and learning at Harapan Bangsa University about how to reduce the intensity of post-operative pain by providing non-pharmacological Benson relaxation therapy.